Pengaruh Penerapan PSAK 72 terhadap Kinerja Keuangan pada Perusahaan Properti yang Terdaftar di BEI Periode 2019-2022 - Dina Islamaya; Rohimah Rohimah; Khaliza Zia; Faisal Nur Khakiki; IIN Rosini (AKUNTANSI 45, 2026)
This study aims to analyze the effect of the implementation of PSAK 72 on the financial performance of property companies listed on the Indonesia Stock Exchange during the 2019–2022 period. PSAK 72, which became effective on January 1, 2020, regulates revenue recognition from contracts with customers and is expected to influence companies that rely on long-term contracts, such as those in the property sector. Financial performance was measured using liquidity, profitability, and solvency ratios, represented by the Current Ratio (CR), Net Profit Margin (NPM), and Debt to Asset Ratio (DAR). This study employed a quantitative descriptive approach with purposive sampling, resulting in 10 property companies and 40 observation data. Secondary data were obtained from annual financial reports published by the Indonesia Stock Exchange. Data analysis was conducted using the MANOVA test with SPSS 22, supported by normality, homogeneity, and covariance matrix homogeneity tests. The findings reveal that the implementation of PSAK 72 does not significantly affect financial performance simultaneously. Partially, PSAK 72 has no significant effect on liquidity and solvency but significantly affects profitability. These results indicate that changes in revenue recognition mainly influence a company’s ability to generate profit rather than its liquidity or capital structure.